Object recognition in fish: accurate discrimination across novel views of an unfamiliar object category (human faces) - Newport, C; Wallis, G; Siebeck, U (Elsevier, 2018)
Accurate visual object recognition is essential to survival for a wide range of species across a wide range of evolutionary histories and visual requirements. However this task is solved, it is a major achievement because object recognition is far from simple. The appearance of an object can alter almost completely as viewing condition change, not least under variations in lighting and orientation. Determining the recognition limits of a species is important to understanding their visual ecology and can help identify conditions under which recognition may fail. In this paper, we test whether a species of fish is able to recognize objects from an unfamiliar object class (human faces) across changes in viewing direction. Using operant conditioning, we trained archerfish (Toxotes chatareus) to discriminate between two frontal views of standardised human faces and, critically, tested whether they could continue to do so as the orientation in depth of the faces changed. All fish learned the initial discrimination task and could also recognize rotated forms. These results represent the first conclusive evidence that a species of fish is able to generalize recognition across views, speaking against a strict image-matching process. The remarkable ability of these fish to generalize recognition across views, speaks to the capacity of relatively simple brains to tackle the hard problem of view-invariance, and provides insight into the mechanisms employed in more complex organisms such as humans. Although we speculate that other fish species may demonstrate similar abilities, a visual system capable of recognition across changes in viewpoint may be especially important to the unique hunting strategy of archerfish.